The level of knowledge of high school students from lubelskie voivodeship about performing first aid - Justyna Wysocka; Marta Pawlicka; Kamil Bałabuszek; Anna Mroczek; Patryk Rzońca; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2018)
Introduction First aid plays a key role in saving human life. It not only prevents the deterioration of the victim's health, but also determines survival. Every year, thousands of people die of various injuries, car accidents and other critical situations. This figure could be significantly lower if the accident witnesses provided first aid to the victims. Material and method Diagnostic survey was selected as the research method, and the research tool was an authorial questionnaire, examining the level of students' knowledge about first aid. It was based on the guidelines of the European Resuscitation Council 2015. The questionnaire consisted of 20 closed single-choice questions and only one of the 4 answers was correct. The obtained results were statistically analyzed using STATISTICA 12 software (StatSoft Polska). For the correlation study the χ2 test was used, and the significance level was taken as p